Wound infiltrating adipocytes are not myofibroblasts - Shruthi Kalgudde Gopal; Ruoxuan Dai; Ania Stefańska; Meshal Ansari; Jiakuan Zhao; Pushkar Ramesh; Johannes Bagnoli; Donovan Correa‐Gallegos; Yue Lin; Simon Christ; Ilias Angelidis; Valerio Lupperger; et al. (2023)
Abstract The origins of wound myofibroblasts and scar tissue remains unclear, but it is assumed to involve conversion of adipocytes into myofibroblasts. Here, we directly explore the potential plasticity of adipocytes and fibroblasts after skin injury. Using genetic lineage tracing and live imaging in explants and in wounded animals, we observe that injury induces a transient migratory state in adipocytes with vastly distinct cell migration patterns and behaviours from fibroblasts. Furthermore, migratory adipocytes, do not contribute to scar formation and remain non-fibrogenic in vitro, in vivo and upon transplantation into wounds in animals. Using single-cell and bulk transcriptomics we confirm that wound adipocytes do not convert into fibrogenic myofibroblasts. In summary, the injury-induced migratory adipocytes remain lineage-restricted and do not converge or reprogram into a fibrosing phenotype. These findings broadly impact basic and translational strategies in the regenerative medicine field, including clinical interventions for wound repair, diabetes, and fibrotic pathologies.